2005
DOI: 10.1002/jmv.20508
|View full text |Cite
|
Sign up to set email alerts
|

Acute hemorrhagic conjunctivitis epidemic caused by coxsackievirus A24 variants in Korea during 2002–2003

Abstract: A variant of coxsackievirus A24 (CA24v) is one of the agents causing acute hemorrhagic conjunctivitis. There was an epidemic of acute hemorrhagic conjunctivitis caused by CA24v in Korea from 2002 to 2003. Seventy‐one strains of CA24v were isolated from 159 conjunctival specimens (45%). Most of the patients were school children under the age of 20. The epidemic began in the first week of August in 2002, and spread extensively, with a peak in the third week of September. CA24v strains were also isolated from con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Therefore, phylogenetic analysis of this region of the sequences from the Spanish and other CV-A24 strains isolated from recent outbreaks of AHC in Korea (2002Korea ( , 2003Korea ( and 2006, China (2002), Tunisia (2003), French Guiana and West Indies (2003), and Singapore (2005), [10][11][12]15 shows all CV-A24 strains from AHC to be phylogenetically close (Fig. 1b).…”
Section: Phylogenetic Analysis Of the Vp1 Genome Regionmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, phylogenetic analysis of this region of the sequences from the Spanish and other CV-A24 strains isolated from recent outbreaks of AHC in Korea (2002Korea ( , 2003Korea ( and 2006, China (2002), Tunisia (2003), French Guiana and West Indies (2003), and Singapore (2005), [10][11][12]15 shows all CV-A24 strains from AHC to be phylogenetically close (Fig. 1b).…”
Section: Phylogenetic Analysis Of the Vp1 Genome Regionmentioning
confidence: 92%
“…8 In recent years, several published reports with molecular studies of outbreaks caused by CV-A24v occurred in Korea (2002) [10][11][12][13][14][15] The phylogenetic analyses published revealed that all these strains were closely related and formed a separate cluster within genotype III.…”
Section: Introductionmentioning
confidence: 97%
“…23 For the 3C pro region, 30 Taiwanese strains were analyzed together with 130 worldwide reference strains in GenBank, including 31 from our previous reports, 23 from China, 16 from South Korea, 17 from Japan, 10 from Singapore (including the EH24 prototype strain), 6 from Guadeloupe, 10 from Morocco, 9 from Congo, 3 from Ghana, 3 from Guiana and 1 each from India, Pakistan and Thailand. 3,4,6,10,11,14,24,25 For VP1 region, 14 Taiwanese strains, 1 Hong Kong strain and 105 worldwide strains were analyzed. The 105 worldwide strains included strains from South Korea (32 strains), Singapore (6, including EH24/70), China (5), Pakistan (5), Algeria (6), Tunisia (8), Spain (10), Sweden (1), Guiana (7), Guadeloupe (4) and USA (1).…”
Section: Phylogenetic Analysis and Evolution Rate Estimationmentioning
confidence: 99%
“…Recently, coxsackievirus A24 variant (CA24v) has been implicated as a major causative agent of AHC outbreaks in many countries. [1][2][3][4][5][6][7][8] In Taiwan, AHC caused by CA24v was characterized by the highest incidence of subconjunctivital hemorrhages (SCHs) among three major aetiological agents of AHC, the other two being Enterovirus 70 (EV70) and adenovirus. 9 Therefore, the reemergence of CA24v is a major public health problem, particularly in heavily populated areas.…”
Section: Introductionmentioning
confidence: 99%
“…It continued with an outbreak in Malaysia the same year (18). In 2003, outbreaks of AHC were reported from South Korea (46), India (19), Nepal (25), Tunisia (60), and Congo (29), and in the western hemisphere from Nicaragua, Honduras, Guatemala, El Salvador, and Caribbean countries (45), French Guiana and the West Indies (15), Puerto Rico (2), and Brazil (38). In 2004, more outbreaks hit both the western (58) and eastern (29) hemispheres.…”
mentioning
confidence: 99%